Biocompatibility of Soldering Materials Used for Repair of Cobalt Chromium Joints - Nadira A Hatim; Nazar Gh Jameel; Abdullah J Mohammed (University of Mosul, College of Dentistry, 2013)
Aims: The aim of this study is to evaluate the biological activities of three soldering materials used for joining Co-Cr joints (iron, stainless steel, and brass) on the tissue of the Rabbit. Materials and Meth-ods: Nine specimens of each iron, stainless steel, and brass where made as cylinders (3mm x 2.5mm). The middle part was made of the brazing materials and the upper and lower parts were made of Co-Cr. These specimens where implanted in the subcutaneous tissue of the rabbit, after two weeks the animals where sacrificed and biopsies where made and examined under microscope by three oral pathologists. Results: Stainless steel implants were the most biocompatible material among the three materials used as brazing materials. Stainless steel sites had insignificant differences with the control sites. Significant difference was found between the iron implanted sites and the control group. This result found by two viewers (A, and M), while the third viewer (Z) found no significant difference between the control group, and the iron implanted sites. Significant difference was found between the brass implanted sites and the control group, this result was found by the three viewers (A, M, and Z). Conclusions: The stainless steel had the most favorable tissue response among the three soldering materials, iron is in the second rank, and brass showed unfavorable tissue response due to release of Cu.